Mental health, stigma, and barriers to care in a Midwestern sample of homeless individuals. Issue 2 (2nd July 2020) - Guenzel, Nicholas; Ivanich, Jerreed; Habecker, Patrick; Struwe, Leeza; Hinrichsen, Shayla
ABSTRACT: The high prevalence of mental health problems among homeless individuals has been well-documented. However, studies have shown significant variability among regions and even cities. As a result, it is necessary to study the mental health of local populations in order to best meet their needs. The current study examined mental health and barriers to accessing care using a cross-sectional, mixed methods, approach. The aims of this study were to describe the prevalence of mental health problems, multiple morbidities, and barriers to accessing mental healthcare in a Midwestern sample of homeless individuals. We recruited 127 individual staying in a homeless shelter in Lincoln, Nebraska and matched them with 127 controls from a national normative data set. We also conducted three focus groups. Mixed methods analysis techniques were used to examine the results. Homeless participants had higher rates of most mental health problems when compared with controls. The greatest disparities were seen in the prevalence of thought problems, internalizing problems, externalizing problems, and obsessive symptoms. Numerous barriers to accessing care were commonly reported with a lack of access being the most commonly cited challenge. Homeless individuals require additional consideration when establishing and providing care given their high rates of multiple morbidities and apparent treatment resistance. Given all the barriers homeless people face, it would be beneficial to establish more accessible methods for individuals to get the help they need.